Risk factors affecting the occurrence of urinary schistosomiasis and urinary tract infections in some communities of Ondo State, Nigeria. (28th December 2022) - Kone, Kikelomo Jennifer; Onifade, Anthony Kayode; Dada, Ebenezer Oluyemi
Abstract: Schistosomiasis is one of the neglected tropical diseases, affecting about 240 million people worldwide. Urinary schistosomiasis (US) is a chronic and debilitating disease caused by blood flukes, Schistosoma haematobium, and people with US are vulnerable to secondary infections caused by bacteria. The study was designed to evaluate the risk factors involved in US and urinary tract infection (UTI) in parts of Ondo State, Nigeria. The study areas were rural communities known to be endemic for schistosomiasis, with farming as their major occupation and they depend solely on the use of the infected rivers for their day to day activities. Structured questionnaires were administered to obtain information concerning the infections. Five hundred and nine community dwellers participated in the study. The results showed that schistosomiasis was significant for gender and age ( X 2 (1) = 23.934, p = 0.000) and ( X 2 (7) = 85.991, p = 0.000), respectively, while UTI was not significant for age and gender. The study revealed that gender, age, contact with infected water, and duration spent in the water were risk factors associated with the development of schistosomiasis and UTI in the communities. HIGHLIGHTS: Frequent contact with infected water induces UTI. Frequent contact with schistosoma infested water causes schistosomiasis. Activities like swimming, fishing, and bathing link people with infected water. School-aged children are more prone to schistosomiasis than other age groups. The higher the time spent in infected water, the more the chance of contracting water borne diseases. Graphical Abstract